Factors Affecting the Level of Disclosure of Islamic Social Reporting (ISR) at Sharia Commercial Banks in Indonesia - Rimi Gusliana Mais; Fajriana Ramadhanty (JFBA: Journal of Financial and Behavioural Accounting, 2021)
This is the study conducted to determine the factors influence the Islamic Social Reporting (ISR) level disclosure at the bank of Islamic Commercial in Indonesia in period of 2016-2020 where the variables are company size (SIZE), profitability (ROA), and company age (AGE). The quantitative method used in this study is a causal research strategy (cause and effect) with panel data regression based on the help of Eviews' 10. All Islamic Commercial Banks who registered in Financial Services Authority (OJK) in 2016 – 2020 is population of this study. The researcher used the method of purposive sampling to choose the sample. The secondary data of this research gained from the reports of financial banking which is downloaded from its website. The researcher analyzed data by using multiple regression test and hypothesis testing. The results of this study indicate that there is a significant positive effect between company size, age and profitability on the level of disclosure in Islamic Social Reporting.